Experimental and computational evaluation of chitosan-Mg2+ augmentation with antibiotics against multi-drug resistant clinical isolates - Rutuja Gumathannavar; Tanu Dixit; Mandar Shirolkar; Laxman Tatikondewar; Anjali Kshirsagar; Neelesh Kumbhojkar; Satish Tongaonkar; Atul Kulkarni; Santosh Koratkar (Nanocomposites)
Antimicrobial resistance is a severe global threat, compromising existing antibiotics’ effectiveness, making infections harder to treat, and increasing illness duration, healthcare costs, and death rates. This highlights the need for novel antimicrobial drugs. Nanomaterials, with their improved stability and bioavailability, offer a promising alternative for treating bacterial infections. This study investigates the synthesis of chitosan-Mg2+ nanocomposites (CS-Mg NC), where Mg2+ is functionalized with chitosan at three different concentrations, and their physicochemical properties are characterized. The nanocomposites’ spherical structure and active binding sites enable Mg2+ ions’ surface functionalization. Density functional theory reveals the interaction between CS and Mg2+, showing changes in binding energy and mechanical strength. Functionalizing Mg2+ with chitosan nanostructures improves the formulation’s cytocompatibility. The synthesized CS-Mg NC efficiently enhances the synergistic effect of nanocomposites and antibiotics against MDR clinical isolates.